Long-Term Chronic Intermittent Hypobaric Hypoxia Induces Glucose Transporter (GLUT4) Translocation Through AMP-Activated Protein Kinase (AMPK) in the Soleus Muscle in Lean Rats - Siques, Patricia; Brito, Julio; Flores, Karen; Ordenes, Stefany; Arriaza, Karem; Pena, Eduardo; León-Velarde, Fabiola; López de Pablo, Ángel L.; Gonzalez, M. C.; Arribas, Silvia (Frontiers in Physiology, 2018)
Background: In chronic hypoxia (CH) and short-term chronic intermittent hypoxia (CIH) exposure, glycemia and insulin levels decrease and insulin sensitivity increases, which can be explained by changes in glucose transport at skeletal muscles involving GLUT1, GLUT4, Akt, and AMPK, as well as GLUT4 translocation to cell membranes. However, during long-term CIH, there is no information regarding whether these changes occur similarly or differently than in other types of hypoxia exposure. This study evaluated the levels of AMPK and Akt and the location of GLUT4 in the soleus muscles of lean rats exposed to long-term CIH, CH and normoxia (NX) and compared the findings. Methods: Thirty male adult rats were randomly assigned to 3 groups: a NX (760 Torr) group (n=10), a CIH group (2 days hypoxia/2 days normoxia; n=10) and a CH group (n=10). Rats were exposed to hypoxia for 30 days in a hypobaric chamber set at 428 Torr (4,600 m). Feeding (10 g daily) and fasting times were accurately controlled. Measurements included food intake (every 4 days), weight, hematocrit, hemoglobin, glycemia, serum insulin (by ELISA) and insulin sensitivity at days 0 and 30. GLUT1, GLUT4, AMPK levels and Akt activation in rat soleus muscles were determined by western blot. GLUT4 translocation was measured with confocal microscopy at day 30. Results: 1) Weight loss and increases in hematocrit and hemoglobin were found in both hypoxic groups (p<0.05). 2) A moderate decrease in glycemia and plasma insulin was found. 3) Insulin sensitivity was greater in the CIH group (p<0.05). 4) There were no changes in GLUT1, GLUT4 levels or in Akt activation. 5) The level of activated AMPK was increased only in the CIH group (p<0.05). 6) Increased GLUT4 translocation to the plasma membrane of soleus muscle cells was observed in the CIH group (p<0.05). Conclusion: In lean rats experiencing long-term CIH, glycemia and insulin levels decrease and insulin sensitivity increases. Interestingly, there is no increase of GLUT1 or GLUT4 levels or in Akt activation. Therefore, cellular regulation of glucose seems to primarily involve GLUT4 translocation to the cell membrane in response to hypoxia-mediated AMPK activation.